Pelatihan Online Psikologi Positif Berbasis Nilai Islam untuk Meningkatkan Resiliensi Mahasiswa - Hapsari, Dian Kusuma; Karyani, Usmi; Hertinjung, Wisnu (Indigenous, 2021)
Abstract. University students are vulnerable to psychological problems, including Muslim university students. One of the reasons is the low resilience level. Therefore, an intervention is needed to develop the resilience of Muslim students so that it is expected to face difficulties and at the same time encourage self-development to protect students from psychological problems. The intervention will be better if it is adjusted to the values held by students, one of which is religious values. However, psychological interventions based on religious values to increase student resilience have not been developed much. This study aims to examine the effect of Islamic-based positive psychology online training on the improvement of university students’ resilience. The training modules were prepared based on the positive psychology intervention techniques and integrated with Islamic values. The training consists of six sessions and was delivered via Zoom meeting. This study employed a quasi-experiment with a one-group design pretest-posttest. The target participants of this study were Muslims students of the Universitas Muhammadiyah Surakarta. Participants who took part in this study received information that was announced through several social media. The study participants were 10 Universitas Muhammadiyah Surakarta students. The Connor-Davidson Resilience Scale (CD-RISC) was used to measure the resilience in Universitas Muhammadiyah Surakarta’s students. The data were analyzed using repeated-measures ANOVA and the results showed the scores of p = 0.005 (p 0.05). This result showed that online positive psychological training with Islamic values improves the university students’ resilience. Online positive psychology training based on Islamic can be used for promotive programs to improve Muslim students' mental health in Indonesia.Keywords: Islamic values; online training; positive psychology; resilience; university students